Genotypic characterization, antimicrobial susceptibility and virulence determinants of Campylobacter jejuni and Campylobacter coli isolated from pastured poultry farms - Awad, Amal; Yeh, Hung-Yueh; Ramadan, Hazem; Rothrock, Michael J. (Frontiers in Microbiology, 2023)
Aim Campylobacter is the leading bacterial pathogen that causes foodborne illnesses worldwide. Pasture farming is regarded as an important source of agricultural production for small farming communities. Consumer preference for pasture-raised animal products has increased; however, there is a paucity of information on the microbiological quality of pasture-raised poultry products. The purpose of this study was to explore genetic relatedness of thermophilic Campylobacter isolates, to assess antibiotic resistance phenotypically and genotypically, and to screen the presence of virulence determinants of Campylobacter isolates from pasture-raised poultry farms from southeastern United States. Methods Ninety-seven Campylobacter isolates previously identified by Q7 BAX® System Real-Time PCR were genotyped by multilocus sequence typing (MLST). Campylobacter isolates were then evaluated for their phenotypic antimicrobial susceptibility against nine antimicrobial agents using Sensititre plates. Additionally, Campylobacter isolates were tested for the presence of antimicrobial resistance-associated elements. Furthermore, Campylobacter isolates were screened for the presence of 13 genes encoding putative virulence factors by PCR. These included genes involved in motility (flaA and flhA), adhesion and colonization (cadF, docC, racR, and virB11), toxin production (cdtA, cdtB, cdtC, wlaN, and ceuE) and invasion (ciaB and iamA). Results Among 97 Campylobacter isolates, Campylobacter jejuni (n = 79) and Campylobacter coli (n = 18) were identified. By MLST, C. jejuni isolates were assigned to seven clonal complexes. Among them, ST-353, ST-607 and ST-21 were the most common STs recognized. All C. coli (n = 18) isolates were included in CC-828. Interestingly, eight STs identified were not belonging any previous identified clonal complex. Campylobacter isolates displayed a high resistance rate against tetracycline (81.4%), while a low rate of resistance was observed against macrolides (azithromycin and erythromycin), quinolones and fluoroquinolones (nalidixic acid and ciprofloxacin), aminoglycosides (gentamicin), ketolide (telithromycin), amphenicol (florfenicol) and lincomycin (clindamycin). Thirteen isolates (13.54%) were pan-susceptible to all tested antibiotics, while nine isolates were multi-antimicrobial resistant (MAR; resist to three or more antimicrobial classes). Interestingly, there were no isolates resistant to all antimicrobial classes. Thr86Ile mutation was identified in all quinolones resistant strains. Erythromycin encoding gene (ermB) was identified in 75% of erythromycin resistant isolates. The A2075 mutation was detected in one erythromycin resistant strain, while A2074 could not be identified. The tetO gene was identified in 93.7% of tetracycline resistant isolates and six tetracycline susceptible isolates. In conclusion, the results of this study revealed that Campylobacter isolates from pasture-raised poultry farms showed the ST relatedness to Campylobacter isolates commonly associated with humans, indicating pasture-raised broiler flocks, similar to conventionally-reared broiler flocks, as a potential vector for antibiotic-resistant and pathogenic strains of thermophilic Campylobacter to humans.